1D portable optical coherence tomography system - Kamińska, Aleksandra Maria; Strąkowski, Marcin (Photonics Letters of Poland, 2018)
Imaging methods are an expanding branch of technology, which involves data acquisition and analysis of images for research and diagnostics. This paper has been devoted to describe the optical design for one-dimensional, portable optical coherence tomography (OCT) system. The Mach-Zehnder interferometer has been designed in the presented study. Description of the construction and applied hardware solutions have been written. Moreover, a dedicated software tools for signal processing and data acquisition have been developed Full Text: PDF References Strąkowski, M. R., Pluciński, J., Jędrzejewska-Szczerska, M., Hypszer, R., Maciejewski, M., Kosmowski, B. B., "Polarization sensitive optical coherence tomography for technical materials investigation", Sensors and Actuators A: Physical 142(1), 104-110 (2008). CrossRef J. G. Fujimoto, W. Drexler, Optical Coherence Tomography: Technology and Applications (Biological and Medical Physics, Biomedical Engineering), (New York, Springer 2008). CrossRef Mujat, M., Chan, R. C., Cense, B., Park, B. H., Joo, C., Akkin, T., De Boer, J. F., "Retinal nerve fiber layer thickness map determined from optical coherence tomography images", Opt. Express 13, 9480-9491 (2005). CrossRef Liang, H., Cid, M. G., Cucu, R. G., Dobre, G. M., Podoleanu, A. G., Pedro, J., Saunders, D., "En-face optical coherence tomography-a novel application of non-invasive imaging to art conservation", Opt. Express 13, 6133-6144 (2005). CrossRef Choma, M. A., Sarunic, M. V., Yang, C., Izatt, J. A., "Sensitivity advantage of swept source and Fourier domain optical coherence tomography", Opt. Express 11, 2183-2189 (2003). CrossRef Koyama, T., Marshek, K. M., "Toothed belt drives—past, present and future", Mechanism and machine theory 23(3), 227-241 (1988). CrossRef Ali, M., & Parlapalli, R., "Signal processing overview of optical coherence tomography systems for medical imaging", Texas Instruments, SPRABB9–June (2010). DirectLink B. E. A. Saleh, M. C. Teich, Fundamentals of Photonics, 2nd Edition (New York, Wiley 1991) CrossRef